Treatment of hepatocellular carcinoma during the COVID‐19 outbreak: The Working Group report of JAMTT‐HCC. Issue 9 (20th July 2020) - Kudo, Masatoshi; Kurosaki, Masayuki; Ikeda, Masafumi; Aikata, Hiroshi; Hiraoka, Atsushi; Torimura, Takuji; Sakamoto, Naoya
Abstract : This contingency guide was formulated on the premise that delivering standard treatment for hepatocellular carcinoma (HCC) has come under strain due to the coronavirus (COVID‐19) pandemic. Measures required are likely to vary largely across regions and individual institutions, depending on the level of the strain imposed by the pandemic (e.g., number of inpatients infected with COVID‐19 and the availability of resources, including personal protective equipment and inpatient beds). In addition, models suggest that the second and third waves of COVID‐19 will occur before effective vaccines and medicines become widely available in Japan (expected time, 2–3 years). This guide should serve as a good reference for best practices in the management of HCC, which is in light of the possible risk of impending collapse of the healthcare system due to a surge in COVID‐19 infections.